Capsicum annum L. Storability Vigor and Estimation of Its Genetic Parameters - Ekowahyuni, Luluk Prihastuti; Sutjahyo, Surjono Hadi; Suhartanto, Mohammad Rahmad; Syukur, Muhammad; Sujiprihati, Sriani (Agro Bali : Agricultural Journal, 2024)
One of the problems of horticultural seeds is the lack of quality of seeds. This experiment aims to evaluate the methods of rapidly pouring hybrid, non-hybrid, local, introduced cayenne pepper seeds and large quantities produced in 2014 and 2016. Non-hybrid seeds were 4 production genotypes in 2014 and 4 in 2016. The hybrid seeds used were 10 production genotypes in 2014 and 8 in 2016. The data analysis used is an analysis of the regression line's angle of inclination, which is the angle resulting from the comparison of the ordinate and abscissa. Based on the results of rapid pouring tests using 20% methanol for 0, 2-, 4-, 6- and 8-hour information, the storability of seeds produced in 2014 was better and higher than in 2016 Therefore, hybrid chili seeds and non-hybrid chili seeds have the same seed storability vigor, as well as between local vs introduced chili seed also large chili seed vs cayenne pepper.